UPAYA GURU PPKn DALAM MENGIMPLEMENTASIKAN SIKAP KEDISIPLINAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI SMP ISLAM DAARUL YAQIIN KOTA SERANG - Ade Millatus Sa'adiyyah; Annisa Nurahmawati (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT This research was conducted at Daarul Yaqiin Islamic Junior High School in Serang City, with the aim of 1) To determine the Efforts of PPKn Teachers in Implementing Discipline Attitudes to Improve Student Learning Achievement in Daarul Yaqiin Islamic Junior High School, Serang City. 2) Knowing the factors that inhibit PPKn Teacher Efforts in Implementing Discipline Attitudes to Improve Student Achievement in Daarul Yaqiin Islamic Junior High School, Serang City. The method used is a qualitative method with data collection through observation, interview and documentation techniques. The analysis used is to use triangulation with data reduction techniques, data display and data fermentation. The results obtained in this study are that the teacher has made an effort to apply disciplinary attitudes quite well by providing a positive attitude to students, applying appropriate rules and sanctions for students, implementing interesting and fun learning for students. While the factors that affect the inhibition of the teacher's efforts in implementing disciplinary attitudes to improve student learning achievement are mainly influenced by two factors, namely internal and external, where internal originates from within the student itself, such as will, habits, physical and psychological factors. Meanwhile, external factors come from the learning environment and social environment.